Dehydration behaviour and structural evolution of graphene oxide membranes on silicon substrate. (April 2017) - Wang, Rui; Gao, Hui; Zhu, Daming; Yang, Tieying; Zhang, Xingmin; Li, Li; Yin, Guangzhi; Zhu, Lina; Feng, Zhenjie; Li, Xiaolong
Abstract: The dehydration kinetics of graphene oxide (GO) were investigated by in-situ two-dimensional grazing incident X-ray diffraction. We found that the interlayer spacing of the GO membrane gradually decreased as the annealing temperature increased and as time elapsed. Surprisingly, we observed the formation of an intermediate "water-rich" GO layers at 25 °C with an interlayer spacing of approximately 15.2 Å, which was caused by the intercalation of two additional layers of water into the interlayers of the GO membrane. Moreover, three types of water trapped in GO were clearly distinguished upon isothermal annealing at various temperatures. Below 160 °C, the removal of "bulk water" and "confined water" resulted in a smaller interlayer spacing and the preservation of oxygen-containing functional groups. At 160 °C or higher, "bound water" was removed and oxygen-containing functional groups were lost, which contributed to the reduction of GO. The dehydration behaviour and structural evolution of GO investigated here is useful for understanding and controlling the properties of GO membranes for permeation, separation and electronic applications. Graphical abstract: